Paradoks Demokrasi di Indonesia: Kerusuhan pada Masa Kampanye Pemilu 1997 - Trijono, Lambang (Jurnal Ilmu Sosial dan Ilmu Politik, 1997)
Democracy in practice ccm prevent political violence in society. Democratic instirutions such as elections can help to avoid political violence because through elections different aspirations among people and groups in society that might become sources of soscial conflict and violence can be resolved institutionally. However, the democracy in Indonesia has become paradoxical. On the one hand, elections have to be held in order to maintain political stability, on the other hand it leaves many social conflict unresolved since political violence are tikely to occur. This article discusses the relationship between democracy political violence in Indonesia.This article focuses on the relationship between the election of 1997 and political riots that erupted during campaign time of the 1997 election. Some political factors related to the 1997 election that caused the riots will also be discussed in this paper. This paper will also propose that practicing more democratic system of government may be able to help prevent political violence in Indonesia.